The Effects Of Differing Density Of Swim-Training Sessions On Shoulder Range Of Motion and Isometric Force Production In National and University Level Swimmers - Matias Yoma; Lee Herrington; Tanya Mackenzie (North American Sports Medicine Institute, 2023)
# Background Well-developed physical qualities (i.e., greater load capacity) in athletes can provide protection against injuries. Although higher competitive level swimmers have more developed physical qualities, no studies have investigated how physical qualities of the shoulder respond to a swim-training session in different competitive levels. # Purpose To compare baseline shoulder external rotation range of motion (ER ROM) and isometric peak torque of the shoulder internal rotators (IR) and external rotators (ER) between national and university level swimmers with differing training volumes. To compare the post-swim changes of these physical qualities between groups. # Study design Cross-sectional. # Methods Ten male swimmers (age= 18.7 ± 1.2 years) were divided into high-load (N= 5 national-level, weekly swim-volume= 37.0 ± 2.7 km) and low-load groups (N= 5 university-level, weekly swim-volume= 6.8 ± 1.8 km). For each group, shoulder active ER ROM and isometric peak torque of the shoulder IR and ER were measured before and immediately after a high-intensity swim-training session (for each group, the hardest swim-session of the week was analyzed). The results were evaluated by the level of significance (p-value), effect size, and whether changes exceeded the measurement error. # Results University-level swimmers had lower baseline ER torque (p= 0.006; d= 2.55) and IR torque (p= 0.011; d= 2.42) than national-level swimmers. For post-swim analysis, ER ROM decreased more in university swimmers (change= -6.3° to -8.4°; d= 0.75-1.05) than national counterparts (change= -1.9° to -5.7°; d= 0.43-0.95). Greater drops in rotation torque were found in university swimmers (IR change= -15% to -21.0%; d= 0.83-1.66; ER change= -9.0% to -17.0%; d= 1.14-1.28) compared to national swimmers (IR change= -10.0% to -13.0%; d= 0.61-0.91; ER change= -3.7% to -9.1%; d= 0.50-0.96). The average change of all tests in university swimmers exceeded the minimal detectable change (MDC), whereas in national level swimmers some tests exceeded the MDC. Despite this, only post-swim ER torque in the dominant side (p= 0.003; d= 1.18) was significantly lower in university swimmers (possibly due to the small sample size). # Conclusions University swimmers have less baseline shoulder external and internal rotator torque and had greater drops of all shoulder physical qualities after a swim-training session, which may have implications for injury risk. However, due to the sample size, the results have to be interpreted with caution. # Level of evidence 3